PROSPECTS FOR USING INDICATORS OF NON-LINEAR ANALYSIS OF HEART RATE VARIABILITY AS MARKERS OF THE FUNCTIONAL STATE OF THE ATHLETE'S BODY WHEN PERFORMING TRAINING AND TESTING LOADS - Fedotova E.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify modern approaches to the use of indicators of non-linear analysis of heart rate variability as markers of the functional state of the athlete's body when performing training and testing loads, indicators of the readiness of body systems to perform a load of a given intensity, criteria for assessing the quality of recovery processes within the framework of operational and routine control measures. Methods and structure of the study. The scientific work used a computerized systematic search for relevant articles from the electronic databases PubMed, Scopus, ResearchGate, Web of Science, eLibrary. Among the initially selected 196 articles met the inclusion criteria and were used for the analysis of 62 papers. Results and conclusions. The prospects of using and potential advantages of non-linear analysis methods as tools for monitoring the functional state of the athlete's body have been studied, and possible limitations of their use in the practice of sports training have been identified. It is shown that one of the most promising methods of nonlinear analysis is the method of detrended fluctuation analysis (DFA), which makes it possible to evaluate the multifractal spectrum of time series and calculate the DFA a1 index; intensity zones, when assessing the functional state of the athlete's body in the pre- and post-load period.